1987
DOI: 10.1073/pnas.84.12.4327
|View full text |Cite
|
Sign up to set email alerts
|

Omega-conotoxin: direct and persistent blockade of specific types of calcium channels in neurons but not muscle.

Abstract: Blockade of Ca2+ channels by ai-conotoxin GVIA, a 27 amino acid peptide from the venom of the marine snail Conus geographus, was investigated with patch-clamp recordings ofwhole-cell and unitary currents in a variety ofcell types. In dorsal root ganglion neurons, the toxin produces persistent block of L-and N-type Cab channels but only transiently inhibits T-type channels. Its actions appear to be neuron-specific, since it blocks high-threshold Ca2' channels in sensory, sympathetic, and hippocampal neurons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
327
7
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(361 citation statements)
references
References 40 publications
23
327
7
2
Order By: Relevance
“…We found that the HVA Ca 2+ current of chick DRG neurons inactivates in a biphasic manner, and that the rapid phase of inactivation is diminished relative to the slow phase when the holding potential from which currents are elicited is depolarized, as others have reported previously (Nowycky et al, 1985;Fox et al, 1987a;Swandulla and Armstrong, 1988). These kinetics cannot be ascribed to the presence of N-and L-type channels as originally suggested (Nowycky et al, 1985) because our studies were confined to t0-CgTx-sensitive, N-type current (Kasai, Aosaki, and Fukuda, 1987;McCleskey, Fox, Feldman, Cruz, Olivera, Tsien, and Yoshikami, 1987;Plummer et al, 1989;Swandulla et al, 1991). Similar inactivation properties have been observed for the N current of rat sympathetic (Plummer et al, 1989), rat DRG (Regan et al, 1991), and frog sympathetic neurons (Jones and Marks, 1989).…”
Section: Discussionmentioning
confidence: 46%
“…We found that the HVA Ca 2+ current of chick DRG neurons inactivates in a biphasic manner, and that the rapid phase of inactivation is diminished relative to the slow phase when the holding potential from which currents are elicited is depolarized, as others have reported previously (Nowycky et al, 1985;Fox et al, 1987a;Swandulla and Armstrong, 1988). These kinetics cannot be ascribed to the presence of N-and L-type channels as originally suggested (Nowycky et al, 1985) because our studies were confined to t0-CgTx-sensitive, N-type current (Kasai, Aosaki, and Fukuda, 1987;McCleskey, Fox, Feldman, Cruz, Olivera, Tsien, and Yoshikami, 1987;Plummer et al, 1989;Swandulla et al, 1991). Similar inactivation properties have been observed for the N current of rat sympathetic (Plummer et al, 1989), rat DRG (Regan et al, 1991), and frog sympathetic neurons (Jones and Marks, 1989).…”
Section: Discussionmentioning
confidence: 46%
“…On the basis of electrophysiological evidence it has been suggested that this toxin blocks both L and N type neuronal VSCC (McCleskey et al, 1987;Cruz et al, 1987), consistent with the suggestion that release is mediated principally by these two channel types (Miller, 1987). However neurotransmitter release has not always been found to be sensitive to co-conotoxin, perhaps reflecting heterogeneity of VSCC between different types of neurone (Anderson & Harvey, 1987;Sano et al, 1987;Maggi et al, 1988).…”
Section: Introductionmentioning
confidence: 74%
“…Thus, application of nifedipine (10 PM), a blocker of L-type Ca 2+ channels, had little effect on the Ca2+ current elicited by a step to 0 mV from a holding potential of -60 mV (mean decrease of 12.5 f 10.5%, mean + SEM; n = 4). In contrast, application of w-conotoxin (16 FM), a blocker of N-type Ca*+ channels (McCleskey et al, 1987;Plummer et al, 1989), inhibited the total Ca*+ current by 70 + 7.6% (n = 5; data not shown). …”
Section: Ss and Ne Inhibit High-threshold Calcium Currentsmentioning
confidence: 94%